Reflection of Traumatic Emotions through Painting: A Cathartic Experience - Liaqat, Sidra; Abbas, Masooma (Pakistan Languages and Humanities Review, 2023)
Creative process is known as a powerful mode of expressing emotions. The research intends to investigate the relationship between traumatic experience and painting, as artist’s emotional outlet. The study delves into probing the cathartic potential of the act of painting. It emphasizes the role of creative expression through painting in regulating and coping with traumatic emotions resulting from an adverse experience. Employing qualitative research methods, the article studies the impact of emotional struggle on artistic expression. Paintings by the Western artists Vincent van Gogh, Edvard Munch, and Frida Kahlo are analyzed in the light of psychological theories after which the paintings of contemporary Pakistani miniaturist Attiya Shaukat are examined. The in-depth examination of her paintings enables to comprehend the process of painting as an outlet of expressing and relieving from traumatic emotions, termed as catharsis. The discourse on artworks by these artists from diverse backgrounds and in different time-frames, signifies the unanimously shared human experience of coping with trauma. The analytical research contributes to the field of art and psychology by highlighting the emotional benefit gained through creative visual expression.